Principles of cloning (Academic Press, 2002)
The book presents the basic biological mechanisms of how cloning works and progresses to discuss current and potential applications in basic biology, agriculture, biotechnology, and medicine. This is the first and most comprehensive book on animal cloning. It includes chapters written by the world's experts in each area. From the early experiments in amphibia to the latest one in mammals, everything is included in this book and told by the researcher that did it and how they did it. It provides basic biological mechanisms on how cloning works and all their current and potential applications. Cloning applications on basic biology, agriculture, biotechnology and medicine are included. The editors are the pioneers in the field.